Social Interactions And Student Achievement In A Developing Country : An Instrumental Variables Approach - Asadullah, Mohammad Niaz, 1975- 1975- (The World Bank, 2008)
This paper identifies endogenous social effects in mathematics test performance for eighth graders in rural Bangladesh using information on arsenic contamination of water wells at home as an instrument. In other words, the identification relies on variation in test scores among peers owing to exogenous exposure to arsenic contaminated water wells at home. The results suggest that the peer effect is significant, and school selection plays little role in biasing peer effects estimates